Effects of Demographic Factors on the Multiple Intelligences of preclinical Dental Students at SEGi University Malaysia - Wong, Rebecca S.Y; Siow, Heng Loke; Vinoth, Kumarasamy; Nazila Shaherah, Fadhullah Suhaimi (2018)
Over the years, there has been an increased emphasis on the learner-centred, outcome-based, as well as patientcentred approach in dental education. These changes require dental students to acquire many hard and soft skills in order to fulfill their role as a health care professional. The Theory of Multiple Intelligences (MI) by Howard Gardner fits well in this changing face of dental education as it embraces a mixed blend of capabilities and skills that are unique to an individual, which are important in shaping the dentist of tomorrow. This cross-sectional study investigated the MI of preclinical dental students at a private university in Malaysia using the MI Inventory. The effects of various demographic factors on MI were also explored. Dental students demonstrated the highest mean score in the intrapersonal domain and the lowest, in the verbal/linguistic domain. Age, gender, race and family income were found to play a role in the MI of these students. Findings of this study gives of a better understanding of the strengths and weaknesses of preclinical dental students in terms of their MI. Demographic and individual differences in MI suggest that mixed modes of teaching and learning and the learner-centred approach are beneficial in dental education.